Good, Bad or Ugly?on the Effects of Fiscal Rules with Creative Accounting - Milesi-Ferretti, Gian (IMF Working Papers; Working Paper, 2000)
Do fiscal rules likely lead to fiscal adjustment, or do they encourage the use of 'creative accounting'? This question is studied with a model in which fiscal rules are imposed on 'measured' fiscal variables, which can differ from 'true' variables because there is a margin for creative accounting. The probability of detecting creative accounting depends on its size and the transparency of the budget. The model studies the effects on fiscal policy of different rules, separating structural from cyclical effects, and examines how these effects depend on the underlying fiscal distortion and on the degree of transparency of the budget.